2018
DOI: 10.4018/ijicte.2018070108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Learning Analytics on Students' Self-Regulated Learning in Flipped Classroom

Abstract: The present article is aimed at analyzing the effects of learning analytics on students' self-regulated learning in a flipped classroom. An experiment was conducted with 96 engineering students, enrolled in a subject offered in the Flipped Classroom model. The students were divided into two groups: an experimental group (N = 51) and a control group (N = 45). After each learning unit, while the control group did not have access to any learning analytics resources, students from the experimental group received a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 29 publications
2
20
0
11
Order By: Relevance
“…The study of [39] initiated the use of learning analytics for improving students self-regulation which supports students in identifying strategies that can increase their academic performance.…”
Section: B What Supports Have Been Proposed To Improve Self-regulatimentioning
confidence: 99%
See 1 more Smart Citation
“…The study of [39] initiated the use of learning analytics for improving students self-regulation which supports students in identifying strategies that can increase their academic performance.…”
Section: B What Supports Have Been Proposed To Improve Self-regulatimentioning
confidence: 99%
“…Self-regulation A system involves: pre-class learning management system, a database, a teacher management system and a self-regulated monitoring system. [34] Self-regulation Technology that uses planned instructional strategies with sustainable support for self-regulation [39] Self-regulation Improving self-regulation through the use of learning analytics which supports students in identifying strategies that can increase their academic performance. [35] Self-regulation Using instant response system (IRS)-facilitated collective issue-quest strategy to engage improve student's self-regulation initiatives in flipped classrooms [38] Online help-seeking Online help-seeking system called 'EchoLu' based on four design principles: Student's alertness of teacher support, promotion of social support, student's needs of privacy in help seeking, improvement of observability peers' help seeking activities [36] Online help-seeking Using online discussion board for offering instant help [37] Online help-seeking Using online discussion board for offering instant help [40] Online help-seeking The use of an Intelligent Tutoring System (ITS) for supporting students in programming tasks…”
Section: B What Supports Have Been Proposed To Improve Self-regulatimentioning
confidence: 99%
“…AlJarrah, Thomas & Shehab, 2018 Gelan et al, 2018Jovanović et al, 2017Hsiao et al, 2018Hui, Mai & Kwok, 2018Lau et al, 2018Sedraz et al, 2018 Fuente: elaboración propia. Melo y Sánchez, 2017 Método mixto para analizar las percepciones de los alumnos sobre la metodología del aula invertida Wang, 2017 Método exploratorio para conocer cómo el comportamiento en línea afecta el rendimiento en el aula invertida Yilmaz, 2017 Método cuantitativo para explorar el impacto de la preparación de aprendizaje electrónico de los estudiantes sobre la satisfacción y motivación en el aula invertida Cochi, 2019 Método experimental y estadístico post hoc informal realizado en un grupo control y un grupo experimental Barral et al, 2018 Método cuantitativo con la prueba de ji-cuadrado para evaluar el aprendizaje de alumnos pertenecientes a un grupo experimental y uno de control Bakla, 2018 Método mixto para un estudio secuencial explicativo para identificar si los materiales generados por el alumno promueven el aprendizaje activo Sergis, Sampson & Pelliccione, 2018 Método cualitativo basado en la teoría de la autodeterminación para explorar el impacto de los entornos de aprendizaje mixtos en el aula invertida Foster & Stagl, 2018 Método mixto basado en encuesta, entrevistas en profundidad y observación a alumnos y maestros para diseñar, implementar y evaluar el aula invertida Mejía et al, 2018. Método cuantitativo, descriptivo y transversal.…”
Section: Resultsunclassified
“…Self-Regulated Learning (SRL) takes the greatest share of mentions, with 10 articles represented (e.g. AlJarrah, Thomas, and Shehab, 2018;Silva et al, 2018;Saint et al, 2018;Fincham et al, 2018;Jovanović et al, 2017;Sun, Lu, and Xie, 2016;Pardo et al, 2015). The SRL theory (Pintrich and Garcia, 1994) establishes that students can have better learning outcomes, cognition, and behaviour with planning, monitoring, and regulating strategies, but also that these strategies are not inherent traits but aptitudes that can be trained.…”
Section: What Were the Educational Outcomes Of Using La In The Fc And Which Theoretical Background Were They Based Upon?mentioning
confidence: 99%
“…Hsiao et al, 2018;Martínez-Muñoz and Pulido, 2015;Smallhorn, 2017;Mouri, Uosaki and Ogata, 2018). Two studies among these especially highlighted the positive impact of students engaging with online feedback on their learning process on higher levels of SRL and better learning outcomes (Matcha et al, 2019;Silva et al, 2018). Some studies succeeded in identifying high performing student groups by correlating their online engagement and assessment performance (Reidsema et al, 2017;Saint, Gašević and Pardo, 2018), and showed that online environments encouraged students' participation in the FC (Hsu, 2019), especially collaborative learning and discussions.…”
Section: What Were the Educational Outcomes Of Using La In The Fc And Which Theoretical Background Were They Based Upon?mentioning
confidence: 99%